2020
DOI: 10.1002/ppp3.10120
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association mapping and comparative genomics identifies genomic regions governing grain nutritional traits in finger millet (Eleusine coracana L. Gaertn.)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 79 publications
(114 reference statements)
1
58
0
Order By: Relevance
“…In foxtail millet, Jaiswal et al [ 40 ] identified 74 marker–trait associations for 10 micronutrient traits through GWAS. Recently, Puranik et al [ 42 ] performed GWAS in finger millet to identify 418 SNPs linked to micronutrient content. These studies should be extended to enable genomics-assisted breeding for the development of improved varieties with high micronutrient content.…”
Section: Mainstreaming Millets For Ensuring Multiple Securities Durinmentioning
confidence: 99%
“…In foxtail millet, Jaiswal et al [ 40 ] identified 74 marker–trait associations for 10 micronutrient traits through GWAS. Recently, Puranik et al [ 42 ] performed GWAS in finger millet to identify 418 SNPs linked to micronutrient content. These studies should be extended to enable genomics-assisted breeding for the development of improved varieties with high micronutrient content.…”
Section: Mainstreaming Millets For Ensuring Multiple Securities Durinmentioning
confidence: 99%
“…( 2014 ); Tiwari et al ( 2020 ) Two-pore channel ( TPC1 ), Ca2 + ATPase , Ca2 + /H + antiporter (CAX1), CaM, CBL, CIPK , and CDPK Uptake, translocation, and accumulation of calcium Calcium biofortification Sharma et al ( 2017 ); Sood et al, 2016 ; Mirza et al. ( 2014 ); Singh et al ( 2014 ) Prolamin‐binding factor DNA binding with one finger only ( PBF Dof ) Nitrogen transport and mobilization in the plant Nitrogen use efficiency Gupta et al ( 2013 ); Gupta et al, 2018 EcNRAMP2, EcNRAMP6, EcPDR9, and EcZTP29, NAM , mitochondrial 3-hydroxyisobutyrate dehydrogenase-like 1 Fe and Zn assimilation in finger millet under stress Fe and Zn biofortification Chandra et al ( 2020 ); Puranik et al ( 2020 ) 2 Foxtail millet Granule-bound starch synthase 1 Physicochemical properties of starch Amylose content Fukunaga et al. ( 2002 ); Bai et al.…”
Section: Deriving Innovations In the Traditional Mixed Cropping Systementioning
confidence: 99%
“…Among the three groups of plants, CAM shows the highest WUE followed by C4 plants (having twice the WUE of C3 species) and C3 plants, respectively. Water use efficiency of crops can be improved by selection of crops according to cropping systems based on available water supplies and increasing seasonal evapo-transpiration (Prihar et al 2000). In the traditional mixed cropping system (Barahnaja) crops are selected based on their stress tolerance and placed as per the availability of water in different fields.…”
Section: Improved Water and Nutrient Use Efficiencymentioning
confidence: 99%
“…However, again the accessions and/or molecular markers involved were generally limited to small numbers, and studies did not have available a finger millet genome assembly to map markers to chromosome positions. These studies include those of Dida et al (2021) who used a medium-sized panel of SNPs but only 52 East African accessions to search for blast disease resistance MTAs; Puranik et al (2020) who used a large panel of SNPs but assessed only 190 genotypes to search for grain nutrient-content-related MTAs; Sharma et al (2018) who applied a medium-sized panel of SNPs to only 113 accessions to search for MTAs in 14 agro-morphological traits; and Tiwari et al (2020) who, beginning with the same SNPs and germplasm panel of Sharma et al (2018), explored marker associations with grain protein content. Despite their limited scope, these previous studies indicated some MTAs.…”
Section: Characterization Of Finger Milletmentioning
confidence: 99%